Proportion of Mutation of Epidermal Growth Factor Receptor (EGFR) Genes from Tissue Biopsy and Liquid Biopsy ctDNA in Lung Adenocarcinoma - Hendra Taufik; Noni Novisari Soeroso; Setia Putra Tarigan; Erna Mutiara (Jurnal Respirologi Indonesia, 2020)
Backgrounds: In recent years, circulating tumor DNA (ctDNA) has emerged as a specific and sensitive blood-based biomarker to detect EGFR mutations. This study aims to determine the diagnostic accuracy of ctDNA in detecting EGFR gene mutations in adenocarcinoma lung cancer. Methods: This study was a cross-sectional study with the subjects were adenocarcinoma lung cancer patients from histopathology or cytology examination and examined EGFR mutations from plasma tissue biopsy and ctDNA specimens from April 2018 to February 2019 in several hospitals in the Medan City. Results: There were 100 data have been collected, with male were 71 subjects and female were 29 subjects. Found 20 mutations, single mutations of tissue biopsy were 19 cases, del exon 19 were 12 cases, mutation in exon 21 (L858R) were 6 cases, mutation exon 21 (L861Q) was 1 case, del exon 19 and 21 (L861Q double mutations) was 1 case. From plasma ctDNA examination EGFR mutations were found 15 cases, del exon 19 were 12 cases and del exon 21 (L858R) were 3 cases. Conclusions: The highest proportion of EGFR mutations by sex were women from tissue biopsy or ctDNA, the most often frequency of EGFR mutations from tissue biopsy and ctDNA in single mutations and exons19. (J Respir Indo. 2020; 40(3): 150-5)